Iowa RBA, November 7-12, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Four emails of Iowa RBA updates for November 7-12, 1999. Highlights of the updates include sightings of a Varied Thrush, Pacific Loon, Red-throated Loon, and a Surf Scoter. Epson - sheet feed/flatbed